Legal Protection of Traditional Knowledge of Indigenous Peoples in Obtaining Economic Benefits, Human Rights Perspertive - Salinding, Marthen B; Irawan, Aris (Universitas Sumatera Utara, 2024)
This research is intended to reveal that traditional knowledge as part of human rights, is the result of innovation and creation of indigenous peoples in terms of knowledge, art, and literature. Traditional knowledge as intellectual property of indigenous peoples is therefore an economic resource that can be utilised for the progress and welfare of indigenous peoples. The research method used is normative juridical with conceptual and statutory approaches. Government efforts in protecting traditional knowledge as intellectual property of indigenous peoples through legislation. Other efforts that can be made are through inventory or documentation of traditional knowledge in an area and can be done by publishing the traditional knowledge as widely as possible. The factor behind the traditional knowledge of indigenous peoples has not provided optimal economic benefits for the welfare of the indigenous peoples concerned is the perspective of the indigenous peoples themselves, namely prioritising the public interest, as well as the lack of knowledge to make traditional knowledge into commodities that provide economic benefits.